Considering Ghararwain's Special Inheritance in the Midst of Gender Justice Issues - Wahidah (Pascasarjana UIN ANTASARI Banjarmasin, 2021)
Abstract: Ghararwain inheritance is a special case of inheritance in Islam that has a fixed heir structure and deviates from faraidh (inheritance law). The application of its calculation method can disadvantage the mother's inheritance rights in two situations. Amidst the issue of gender equality, various perspectives from different professions, expertise, and viewpoints show diverse responses, yet adaptive to change. This ijtihadi product, although possessing wisdom related to maqashid al sharia (the objectives of Islamic law), needs to be reconsidered for its use as a provision for inheritance settlement in positive law in Indonesia, especially concerning the tsuluts al baqi portion (one-third of the remaining estate) which serves as a privilege in the Ghararwain case. Keywords: Special Inheritance, Ghararwain, Ashobah, Tsuluts al Baqi, Gender Equality